2017
DOI: 10.1158/1541-7786.mcr-17-0063
|View full text |Cite
|
Sign up to set email alerts
|

Combined AURKA and H3K9 Methyltransferase Targeting Inhibits Cell Growth By Inducing Mitotic Catastrophe

Abstract: The current integrative pathobiological hypothesis states that pancreatic cancer (PDAC) develops and progresses in response to an interaction between known oncogenes and downstream epigenomic regulators. Congruently, this study tests a new combinatorial therapy based on the inhibition of the Aurora kinase A (AURKA) oncogene and one of its targets, the H3K9 methylation-based epigenetic pathway. This therapeutic combination is effective at inhibiting the in vitro growth of PDAC cells both, in monolayer culture s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Moreover, combination treatment with the pan-H3K9me HMT inhibitor chaetocin and an aurora kinase A (AURKA) inhibitor diminishes H3K9 methylation at centromeres, induces mitotic aberrations, triggers an abnormal mitotic checkpoint response, and ultimately leads to mitotic catastrophe in PC. 222 At the same time, the prospect of arginine methylation as a therapeutic target has been revealed gradually. For example, a recent study found that targeting PRMT5 activity by DW47800 inhibits the malignancy of HCC by downregulating the binding of H4R3me2s to the HNF4α promoter.…”
Section: Clinical Application Of Histone Methylation In Digestive Canmentioning
confidence: 99%
“…Moreover, combination treatment with the pan-H3K9me HMT inhibitor chaetocin and an aurora kinase A (AURKA) inhibitor diminishes H3K9 methylation at centromeres, induces mitotic aberrations, triggers an abnormal mitotic checkpoint response, and ultimately leads to mitotic catastrophe in PC. 222 At the same time, the prospect of arginine methylation as a therapeutic target has been revealed gradually. For example, a recent study found that targeting PRMT5 activity by DW47800 inhibits the malignancy of HCC by downregulating the binding of H4R3me2s to the HNF4α promoter.…”
Section: Clinical Application Of Histone Methylation In Digestive Canmentioning
confidence: 99%
“…Images were acquired on a Hamamatsu digital camera using AmtV602 image processing software. Immunofluorescence and confocal microscopy were performed as described previously (12). Primary antibodies are indicated in Supplementary Table S1, followed by anti-mouse or anti-rabbit secondary antibody, as appropriate.…”
Section: Electron and Immunofluorescence Microscopymentioning
confidence: 99%
“…However, most of these agents are being studied within the framework of their gene regulatory activity without taking into consideration their effects during the distinct cell-cycle phases, which we believe to be critical for better understanding cancer. In fact, we have recently shown that arresting cells in G 2 -M with an Aurora kinase A inhibitor while combining them with an inhibitor of the epigenetic H3K9 methylation pathway is an effective approach for altering chromatin structure in a manner that gives rise to an aberrant mitotic checkpoint response leading to rapid death (12). This approach suggested that the capacity of cell-cycle inhibitors could be harnessed to enhance the use of epigenetic inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Mathison et al have shown that inhibition of the H3K9 methyltransferase SUV39H1/2, can reduce the growth of PDAC cells in monolayer cells culture, as well as in spheroids, organoids and grafts in vivo. Combined inhibition of AURKA using MLN8237 and H3K9 methyltransferases using a pan-histone methyltransferase inhibitor, chaetocin, induced mitotic catastrophe and proved to be efficacious in preventing progression of the various aforementioned PDAC models [ 61 ]. Gossypol, a chemotherapeutic under investigation, has been used in combination with BRD-4770 to induce autophagy related death [ 50 ].…”
Section: Targeting Histone Modificationsmentioning
confidence: 99%